Implications of Applying New Technology in Cosmetic and Reconstructive Facial Plastic Surgery - Qureshi, Uneeb Ahmed; Calaguas, Shannon; Frank, Ethan; Inman, Jared (Facial Plastic Surgery, 2020)
The field of facial plastic and reconstructive surgery is privy to a myriad of technological advancements. As innovation in areas such as imaging, computer applications, and biomaterials progresses at breakneck speed, the potential for clinical application is endless. This review of recent progress in the implementation of new technologies in facial plastic surgery highlights some of the most innovative and impactful developments in the past few years of literature. Patient-specific surgical modeling has become the gold standard for oncologic and posttraumatic reconstructive surgery, with demonstrated improvements in operative times, restoration of anatomical structure, and patient satisfaction. Similarly, reductions in revision rates with improvements in learner technical proficiency have been noted with the use of patient-specific models in free flap reconstruction. In the cosmetic realm, simulation-based rhinoplasty implants have drastically reduced operative times while concurrently raising patient postoperative ratings of cosmetic appearance. Intraoperative imaging has also seen recent expansion in its adoption driven largely by reports of eradication of postoperative imaging and secondary—often complicated—revision reconstructions. A burgeoning area likely to deliver many advances in years to come is the integration of bioprinting into reconstructive surgery. Although yet to clearly make the translational leap, the implications of easily generatable induced pluripotent stem cells in replacing autologous, cadaveric, or synthetic tissues in surgical reconstruction are remarkable.
Keywords: 3D printing; patient modeling; augmentation; bioprinting; image capturing